Statistical data analysis for budget planning in the provision of medical and social rehabilitation injured persons - Fedorenko, S.M.; Chadyuk, A.V. (Інститут програмних систем НАН України, 2015)
This work describes the one of possible implementation variant of the statistical data analysis for budget planning in the provision of medical and social rehabilitation injured persons. It offers the variant of the algorithm realization in the information system. The main tasks of system development and enlargement of information databases are defined in the article/